Clinical Characteristics of Endogenous Cushing's Syndrome at a Medical Center in Southern Taiwan. (22nd August 2013) - Tung, Shih-Chen; Wang, Pei-Wen; Liu, Rue-Tsuan; Chen, Jung-Fu; Hsieh, Ching-Jung; Kuo, Ming-Chun; Yang, Joseph W.; Lee, Wei-Ching; Cheng, Min-Hsiung; Lee, Tao-Chen
Abstract : From January 1987 to December 2011, over a total of 25 years, 84 patients with Cushing's syndrome (CS) were identified at a medical center in southern Taiwan. We observed a higher incidence of ACTH-independent CS (75%) than ACTH-dependent CS (25%). A higher incidence of adrenocortical adenoma (58.3%) than Cushing's disease (CD, 21.4%) was also found. The sensitivity of the definitive diagnostic tests for CS, including loss of plasma cortisol circadian rhythm, a baseline 24 h urinary free cortisol (UFC) value >80  μ g, and overnight and 2-day low-dose dexamethasone suppression test, was between 94.4% and 100%. For the 2-day high-dose dexamethasone suppression test for the differential diagnosis of CD, the sensitivity of 0800 h plasma cortisol and 24 h UFC was 44.4% and 85.7%, respectively. For the differential diagnosis of adrenal CS, the sensitivities of the 0800 h plasma cortisol and 24 h UFC were 95.5% and 88.9%, respectively. In patients with ACTH-independent CS and ACTH-dependent CS, the baseline plasma ACTH levels were all below 29 pg/mL and above 37 pg/mL, respectively. The postsurgical hospitalization stay following retroperitoneoscopic adrenalectomy was shorter than that observed for transabdominal adrenalectomy (4.3 ± 1.6 versus 8.8 ± 3.7 days, P < 0.001 ). It was easy to develop retroperitoneal and peritoneal seeding of adrenocortical carcinoma via laparoscopic adrenalectomy.